2019
DOI: 10.22521/edupij.2019.83.2
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Language Teaching and Learning in Kenya in the Prospects of China’s Reform and Opening-up

Abstract: Teaching and learning of Chinese as a foreign language and its culture is complex for Kenyan learners. It requires them to consider contrasting intellectual, policy and economic dimensions that instead of aiding its propagation among Kenyan learners, could even facilitate a hindrance to its progression. Potential measures that could be embraced are examined in this study based on the current context in lieu of proper guidelines or policy for foreign language learning, and in the midst of China's reform and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…Notably, the teachers indicated that parents today want their children to learn Mandarin Chinese language because of China's economic growth and investment in the Zambian economy and most parents have no objection to the introduction of Mandarin Chinese language in the schools today. This finding agrees with Owaki, Kathina, Khayeka-Wandabwa, Gichuru, and Amimo (2019) who argued that Chinese language has become valued as one of the promising foreign language in Africa today and has become a driving force for many Mandarin Chinese language learners due to the economic gain prospect in the future.…”
Section: Motivation and Beliefssupporting
confidence: 90%
“…Notably, the teachers indicated that parents today want their children to learn Mandarin Chinese language because of China's economic growth and investment in the Zambian economy and most parents have no objection to the introduction of Mandarin Chinese language in the schools today. This finding agrees with Owaki, Kathina, Khayeka-Wandabwa, Gichuru, and Amimo (2019) who argued that Chinese language has become valued as one of the promising foreign language in Africa today and has become a driving force for many Mandarin Chinese language learners due to the economic gain prospect in the future.…”
Section: Motivation and Beliefssupporting
confidence: 90%